Calibration of Novel Protein Biomarkers for Veterinary Clinical Pathology: A Call for International Action - Eckersall, Peter David (Frontiers in Veterinary Science, 2019)
Research into the identification and use of protein biomarkers for use in veterinary clinical pathology has produced numerous potential analytes that could become common tests in the future. One problem that has to be overcome in the general acceptance of a novel biomarker is that differing standards for calibration may be developed by individual laboratories or the diagnostic companies that will provide kits for widespread use. This has been apparent in the development of acute phase protein biomarkers such as canine C-reactive protein. In order to overcome this problem an international initiative is required to ensure that assays developed in separate laboratories would have a consistent calibration protocol so that results produced are equivalent. International reference preparations for serum protein analysis for each relevant species should be established for use as primary standard in the calibration of biomarkers for veterinary diagnosis.